Density domains of a photo-excited electron gas on liquid helium - Monarkha, Yu.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The Coulombic effect on the stability range of the photo-excited electron gas on liquid helium is shown to favor formation of domains of different densities. Domains appear to eliminate or greatly reduce regions with negative conductivity. An analysis of the density domain structure allows explaining remarkable observations re-ported recently for the photo-excited electron gas.